Multi-disciplinary Trends in Artificial Intelligence 9th International Workshop, MIWAI 2015, Fuzhou, China, November 13-15, 2015, Proceedings - Bikakis, Antonis; Zheng, Xianghan (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes the refereed conference proceedings of the 9th International Conference on Multi-disciplinary Trends in Artificial Intelligence, MIWAI 2015, held in Fuzhou, China, in November 2015. The 30 revised full papers presented together with 12 short papers were carefully reviewed and selected from 83 submissions. The papers feature a wide range of topics covering knowledge representation, reasoning, and management; multi-agent systems; data mining and machine learning; computer vision; robotics; AI in bioinformatics; AI in security and networks; and other AI applications.